Layout, Topology, and Size Optimization of Steel Frame Design Using Metaheuristic Algorithms: A Comparative Study - Doddy Prayogo; Hasan Santoso; Franky Budiman; Marcellino Jason (Civil Engineering Dimension, 2022)
Determining the topology, layout, and size of structural elements is one of the most important aspects in designing steel seismic-resistant structures. Optimization of these parameters is beneficial to find the lightest weight of the structure, thus reducing construction cost. This study compares the performance of three metaheuristic algorithms, namely, Particle Swarm Optimization (PSO), Symbiotic Organisms Search (SOS), and Differential Evolution (DE). Three study cases are used in order to find the lightest structural weight without violating constraints based on SNI 1726:2019, SNI 1729:2020, and SNI 7860:2020. The results of this study show that SOS has better performance than other algorithms.